Modified polyether-ether-ketone composite material and preparation method thereof
By preparing modified polyether ether ketone composite materials, combined with carbon fiber, modified nanosilica and modified compatibility agent, the problem of insufficient performance of existing PEEK materials under friction conditions is solved, and better mechanical and physical properties are achieved.
Patent Information
- Application Number
- CN202510333932.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-20
AI Technical Summary
The performance of existing polyether ether ketone (PEEK) materials under friction conditions has limitations, such as high friction coefficient, insufficient wear resistance, and it is difficult for traditional processing technology to achieve complex shape customization.
By preparing a modified polyether ether ketone composite material, including polyether ether ketone resin, carbon fiber, modified nanosilica, hydroxyapatite, coupling agent and modification compatibilizer, mixing and forming using a high-speed mixer and twin-screw extruder.
The tensile properties, friction properties and thermal deformation temperature of the composite material are improved, the mechanical properties and physical properties of the material are enhanced, and the customization of complex shapes is achieved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a modified polyetheretherketone composite material and a preparation method thereof. Background Art
[0002] Polyetheretherketone (PEEK) is a semi-crystalline thermoplastic polymer known for its high temperature resistance (melting temperature 334°C), chemical stability, mechanical strength and self-lubricity. It is widely used in aerospace, automotive, electronics and medical fields. Its linear aromatic molecular structure gives it high wear resistance and dimensional stability, especially in the field of tribology. However, the performance of pure PEEK materials under friction conditions is still limited, such as high friction coefficient, insufficient wear resistance, and traditional processing technology is difficult to achieve complex shape customization. Existing PEEK modification technology mainly improves its performance by adding fillers (such as carbon fiber, glass fiber, nanoparticles, etc.), but there are problems such as poor compatibility between PEEK and fillers, poor dispersion of fillers, weak interface bonding, and insufficient biological activity. Therefore, it is of great significance to develop a modified PEEK composite material with better comprehensive performance.
[0003] The Chinese invention patent with publication number CN109851989A discloses a polyetheretherketone composite material and its preparation method and application, wherein the polyetheretherketone composite material comprises the following components: 60-75 parts of polyetheretherketone; 5-10 parts of polytetrafluoroethylene; 5-15 parts of polyimide; 5-10 parts of carbon fiber; 0.1-1 parts of graphene; and 0.5-4 parts of nano-silicon dioxide. The polyetheretherketone composite material prepared by the invention has good high temperature resistance, but its tensile and friction properties are poor. Summary of the invention
[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a modified polyetheretherketone composite material and a preparation method thereof.
[0005] To achieve the above object, the present invention is implemented through the following technical solutions: A modified polyetheretherketone composite material comprises the following raw materials in parts by weight: Polyetheretherketone resin: 60-85 parts; carbon fiber: 5-15 parts; modified nano-silica: 5-20 parts; hydroxyapatite: 5-10 parts; coupling agent: 0.5-2 parts; modified compatibilizer: 2-4 parts; The modified compatibilizer is prepared by the following method: S1: p-Hydroxyacetophenone and 2-chloro-5-nitro-trifluoromethylbenzene undergo nucleophilic substitution reaction in the presence of anhydrous K2CO3 to give intermediate 1; S2: Under the action of catalyst silicon tetrachloride, three molecules of intermediate 1 are condensed to undergo benzene cyclization reaction to obtain a trinitro compound; S3: The trinitro compound is reduced to a fluorine-containing triamine monomer under the action of a catalyst Pd / C and a reducing agent hydrazine hydrate; S4: Under nitrogen protection, add DMAc and fluorinated triamine monomer into the reactor, slowly drop 4,4'-(hexafluoroisopropylene) diphthalic anhydride, stir and react for 12-24 hours, then add acetic anhydride / pyridine mixture, and carry out ring-closing reaction at room temperature to obtain the modified compatibilizer.
[0006] In the step S1, the mass ratio of p-hydroxyacetophenone to 2-chloro-5-nitro-trifluoromethylbenzene is 1:(1-1.25).
[0007] In the step S2, the feed mass ratio of the intermediate 1 to silicon tetrachloride is 20:(4-6).
[0008] In the step S3, the mass ratio of the trinitro compound, Pd / C and hydrazine hydrate is 20:(0.6-0.8):(5-8).
[0009] In the step S4, the feed mass ratio of DMAc, fluorine-containing triamine monomer, and 4,4'-(hexafluoroisopropylene) diphthalic anhydride is 50:(12-16):(8-10).
[0010] The coupling agent is one of vinyl triethoxysilane, 3-glycidyloxypropyl trimethoxysilane, and methyl vinyl dimethoxysilane, or a combination of several thereof.
[0011] The preparation method of the modified nano silicon dioxide is as follows: S1: Add toluene and nano-silica to the reactor, perform ultrasonic vibration for 20-30 minutes, then add γ-methacryloxypropyltrimethoxysilane and triethylamine, react at 100-120°C for 3-5 hours, and post-treat to obtain silane-grafted nano-silica; S2: Under nitrogen protection, toluene, silane-grafted nano-silica, styrene and initiator AIBN are added into the reactor, stirred and mixed, heated to 80-100° C., reacted for 12-16 hours, and post-treated to obtain modified nano-silica.
[0012] In step S1, the mass ratio of toluene, nano-silica and γ-methacryloxypropyltrimethoxysilane is 50:(12-16):(4-6).
[0013] In step S2, the mass ratio of toluene, silane-grafted nano-silica, styrene, and initiator AIBN is 50:(8-10):(2-3):(0.02-0.05).
[0014] A method for preparing a modified polyetheretherketone composite material comprises the following steps: S1: Weigh, by weight, 60-85 parts of polyetheretherketone resin; 5-15 parts of carbon fiber; 5-20 parts of modified nano-silicon dioxide; 5-10 parts of hydroxyapatite; 0.5-2 parts of coupling agent; and 2-4 parts of modified compatibilizer; S2: Add polyetheretherketone resin, carbon fiber, modified nano-silica, hydroxyapatite, coupling agent, and modified compatibilizer into a high-speed mixer in proportion and mix evenly; add the mixture into a twin-screw extruder, set the melt temperature to 360-400°C, the screw speed to 200-400rpm, and extrude granulation; injection mold the granular material, the injection temperature to 350-380°C, the mold temperature to 160-180°C, and obtain a modified polyetheretherketone composite material.
[0015] Due to the adoption of the above technical solution, the beneficial effects of the present invention include: (1) The present invention provides an intermediate 1 by a nucleophilic substitution reaction between p-hydroxyacetophenone and 2-chloro-5-nitro-trifluoromethylbenzene; the intermediate 1 undergoes a benzene cyclization reaction to obtain a trinitro compound; the trinitro compound is reduced to a fluorine-containing triamine monomer under the action of hydrazine hydrate; and then the fluorine-containing triamine monomer reacts with 4,4'-(hexafluoroisopropylene) diphthalic anhydride to prepare a modified compatibilizer.
[0016] (2) The present invention prepares silane-grafted nano-silica by grafting a silane coupling agent, γ-methacryloxypropyltrimethoxysilane, on the surface of nano-silica, and then grafting styrene to prepare modified nano-silica.
[0017] (3) The structural units such as the fluorine-containing triamine monomer in the modified compatibilizer prepared by the present invention have good flexibility and reactivity, and can form a "bridge" between polyetheretherketone and other components, reduce the interfacial energy between the phases, enhance the interfacial bonding force, make the distribution of the various phases inside the composite material more uniform, and improve the overall performance. The modified compatibilizer can reduce the surface tension between the phases, prevent particle agglomeration, promote the good dispersion of the reinforcing phase (such as carbon fiber, etc.) in the polyetheretherketone matrix, make the composite material more uniform in microstructure, and thus improve the mechanical and physical properties of the material.
[0018] (4) Through silane coupling agent and styrene grafting treatment, the surface hydroxyl groups are replaced by hydrophobic groups, the polarity is reduced, and the compatibility with the polyetheretherketone matrix is improved. After the modified nano-silica is evenly dispersed, it forms a three-dimensional network with the matrix molecular chain through physical entanglement or chemical cross-linking, which can effectively disperse the external load and improve the tensile strength of the material. DETAILED DESCRIPTION
[0019] The invention will be further described below in conjunction with the embodiments, but the invention is not limited to these embodiments.
[0020] Example 1 Preparation of modified compatibilizer: S1: Under nitrogen protection, add 400 ml DMAc, 40 g p-hydroxyacetophenone, and 50 g anhydrous K2CO3 to the reactor, stir and mix, heat to 120°C, then slowly drop 40 g 2-chloro-5-nitro-trifluoromethylbenzene, drop for 10 min, react for 10 h, cool to 40°C, add 100 ml anhydrous ethanol and 600 ml deionized water, stir, precipitate, filter, and then wash three times with deionized water (50 ml of deionized water each time), then add 300 ml anhydrous ethanol for recrystallization, and dry under vacuum at 70°C for 2 h to obtain intermediate 1; S2: Add 200 ml of anhydrous ethanol and 20 g of intermediate 1 to the reactor, stir, slowly and uniformly add 4 g of silicon tetrachloride at room temperature for 2 min, react at room temperature for 12 h, then add 100 ml of deionized water, continue stirring for 30 min, slowly add 10 wt% NaOH solution to adjust the solution to neutrality, filter, add 80 ml of deionized water for washing, and dry in vacuo at 60 ° C for 2 h to obtain a trinitro compound; S3: Under nitrogen protection, add 200 ml of anhydrous ethanol, 20 g of a trinitro compound, and 0.6 g of Pd / C to the reactor, stir and mix, heat to reflux, then slowly drop 5 g of hydrazine hydrate for 30 min, react for 12 h, cool to room temperature, add 200 ml of deionized water, stir, precipitate, filter, and then wash three times with deionized water (50 ml of deionized water each time), and vacuum dry at 50 ° C for 4 h to obtain a fluorinated triamine monomer, whose structural formula is as follows:
[0021] Its nuclear magnetic resonance hydrogen spectrum data are as follows: 1 H NMR (500 MHz, Chloroform-d) δ 7.81 (s, 3H), 7.59-7.46 (m, 6H), 7.24 (dt, J = 1.9, 0.9 Hz, 3H), 7.20-7.13 (m, 6H), 7.00 (d, J = 8.1 Hz, 3H), 6.62 (dd, J = 8.1, 2.2 Hz, 3H), 4.73 (s, 6H). S4: Under nitrogen protection, add 500g DMAc and 120g fluorine-containing triamine monomer into the reactor, add 80g 4,4'-(hexafluoroisopropylene) diphthalic anhydride in batches (20g in each batch, 5min interval between batches), stir, react at room temperature for 12h, then add 300ml acetic anhydride / pyridine mixture (acetic anhydride: pyridine (V:V) = 4:5), react at room temperature for 12h, then add 500ml anhydrous ethanol to produce precipitation, filter, wash with 35ml deionized water, and vacuum dry at 60℃ for 3h to obtain the modified compatibilizer.
[0022] Example 2 Preparation of modified compatibilizer: S1: Under nitrogen protection, add 400 ml DMAc, 40 g p-hydroxyacetophenone, and 55 g anhydrous K2CO3 to the reactor, stir and mix, heat to 110°C, then slowly drop 45 g 2-chloro-5-nitro-trifluoromethylbenzene, drop for 12 min, react for 11 h, cool to 40°C, then add 100 ml anhydrous ethanol and 600 ml deionized water, stir, precipitate, filter, and then wash three times with deionized water (50 ml of deionized water each time), then add 300 ml anhydrous ethanol for recrystallization, and dry under vacuum at 60°C for 3 h to obtain intermediate 1; S2: Add 200 ml of anhydrous ethanol and 20 g of intermediate 1 to the reactor, stir, slowly and uniformly add 5 g of silicon tetrachloride at room temperature for 2 min, react at room temperature for 13 h, then add 100 ml of deionized water, continue stirring for 30 min, slowly add 10 wt% NaOH solution to adjust the solution to neutrality, filter, add 80 ml of deionized water for washing, and vacuum dry at 50 ° C for 3 h to obtain a trinitro compound; S3: Under nitrogen protection, add 200 ml of anhydrous ethanol, 20 g of a trinitro compound, and 0.7 g of Pd / C to the reactor, stir and mix, heat to reflux, and then slowly drop 6 g of hydrazine hydrate for 45 min. After reacting for 11 h, cool to room temperature, add 200 ml of deionized water, stir, precipitate, filter, and then wash three times with deionized water (50 ml of deionized water each time), and vacuum dry at 60 ° C for 3 h to obtain a fluorine-containing triamine monomer; S4: Under nitrogen protection, add 500g DMAc and 140g fluorine-containing triamine monomer into the reactor, add 90g 4,4'-(hexafluoroisopropylene) diphthalic anhydride in batches (30g in each batch, 5min interval between batches), stir, react at room temperature for 14h, then add 300ml acetic anhydride / pyridine mixture (acetic anhydride: pyridine (V:V) = 4:5), react at room temperature for 14h, then add 500ml anhydrous ethanol to produce precipitation, filter, wash with 35ml deionized water, and dry in vacuo at 50℃ for 4h to obtain the modified compatibilizer.
[0023] Example 3 Preparation of modified compatibilizer: S1: Under nitrogen protection, add 400 ml DMAc, 40 g p-hydroxyacetophenone, and 60 g anhydrous K2CO3 to the reactor, stir and mix, heat to 100°C, then slowly drop 50 g 2-chloro-5-nitro-trifluoromethylbenzene, drop for 15 min, react for 12 h, cool to 40°C, then add 100 ml anhydrous ethanol and 600 ml deionized water, stir, precipitate, filter, and then wash three times with deionized water (50 ml of deionized water each time), then add 300 ml anhydrous ethanol for recrystallization, and dry under vacuum at 50°C for 4 h to obtain intermediate 1; S2: Add 200 ml of anhydrous ethanol and 20 g of intermediate 1 to the reactor, stir, slowly and uniformly add 6 g of silicon tetrachloride at room temperature for 2 min, react at room temperature for 14 h, then add 100 ml of deionized water, continue stirring for 30 min, slowly add 10 wt% NaOH solution to adjust the solution to neutrality, filter, add 80 ml of deionized water for washing, and dry in vacuo at 40 ° C for 4 h to obtain a trinitro compound; S3: Under nitrogen protection, add 200 ml of anhydrous ethanol, 20 g of a trinitro compound, and 0.8 g of Pd / C to the reactor, stir and mix, heat to reflux, and then slowly drop 8 g of hydrazine hydrate for 1 hour. After reacting for 10 hours, cool to room temperature, add 200 ml of deionized water, stir, precipitate, filter, and then wash three times with deionized water (50 ml of deionized water each time), and vacuum dry at 70°C for 2 hours to obtain a fluorinated triamine monomer; S4: Under nitrogen protection, add 500g DMAc and 160g fluorine-containing triamine monomer into the reactor, add 100g 4,4'-(hexafluoroisopropylene) diphthalic anhydride in batches (25g in each batch, 5min interval between batches), stir, react at room temperature for 16h, then add 300ml acetic anhydride / pyridine mixture (acetic anhydride: pyridine (V:V) = 4:5), react at room temperature for 16h, then add 500ml anhydrous ethanol to produce precipitation, filter, wash with 35ml deionized water, and dry in vacuo at 70℃ for 2h to obtain the modified compatibilizer.
[0024] Example 4 Preparation of modified nano-silicon dioxide: S1: Add 500g toluene and 120g nano-silica into the reactor, ultrasonically shake for 20min, then add 40g γ-methacryloxypropyltrimethoxysilane and 60ml triethylamine, react at 100°C for 5h, centrifuge and wash, wash with 100ml toluene, 100ml anhydrous ethanol, 100ml 50wt% ethanol in sequence, and then vacuum dry at 80°C for 2h to obtain silane-grafted nano-silica; S2: Under nitrogen protection, add 500g toluene, 80g silane-grafted nano-silica, 20g styrene and 0.2g initiator AIBN into the reactor, stir and mix, heat to 80°C, react for 16h, then cool to room temperature, add 500ml methanol, let stand and precipitate, filter, and dry in vacuo at 80°C for 5h to obtain modified nano-silica.
[0025] Example 5 Preparation of modified nano-silicon dioxide: S1: Add 500g toluene and 140g nano-silica into the reactor, ultrasonically shake for 25min, then add 50g γ-methacryloxypropyltrimethoxysilane and 65ml triethylamine, react at 110°C for 4h, centrifuge and wash, wash with 100ml toluene, 100ml anhydrous ethanol, 100ml 50wt% ethanol in sequence, and then vacuum dry at 90°C for 1h to obtain silane-grafted nano-silica; S2: Under nitrogen protection, add 500g toluene, 90g silane-grafted nano-silica, 25g styrene and 0.3g initiator AIBN into the reactor, stir and mix, heat to 90°C, react for 14h, then cool to room temperature, add 500ml methanol, let stand and precipitate, filter, and dry under vacuum at 70°C for 6h to obtain modified nano-silica.
[0026] Example 6 Preparation of modified nano-silicon dioxide: S1: Add 500g toluene and 160g nano-silica into the reactor, ultrasonically shake for 30min, then add 60g γ-methacryloxypropyltrimethoxysilane and 70ml triethylamine, react at 120°C for 3h, centrifuge and wash, wash with 100ml toluene, 100ml anhydrous ethanol, 100ml 50wt% ethanol in sequence, and then vacuum dry at 100°C for 40min to obtain silane-grafted nano-silica; S2: Under nitrogen protection, add 500g toluene, 100g silane-grafted nano-silica, 30g styrene and 0.5g initiator AIBN into the reactor, stir and mix, heat to 100°C, react for 12h, then cool to room temperature, add 500ml methanol, let stand and precipitate, filter, and dry under vacuum at 60°C for 7h to obtain modified nano-silica.
[0027] Example 7 Preparation of modified polyetheretherketone composite material: S1: Weigh polyetheretherketone resin: 600g; carbon fiber: 50g; modified nano-silica (prepared in Example 4): 50g; hydroxyapatite: 50g; coupling agent (3-glycidyloxypropyltrimethoxysilane): 5g; modified compatibilizer (prepared in Example 1): 20g; S2: Add polyetheretherketone resin, carbon fiber, modified nano-silica, hydroxyapatite, coupling agent, and modified compatibilizer into a high-speed mixer in proportion and mix evenly; add the mixture into a twin-screw extruder, set the melt temperature to 360°C, the screw speed to 200rpm, and extrude granules; injection mold the granular material, the injection temperature to 350°C, the mold temperature to 160°C, and obtain a modified polyetheretherketone composite material.
[0028] Example 8 Preparation of modified polyetheretherketone composite material: S1: Weigh polyetheretherketone resin: 700g; carbon fiber: 80g; modified nano-silica (prepared in Example 5): 120g; hydroxyapatite: 80g; coupling agent (vinyltriethoxysilane): 10g; modified compatibilizer (prepared in Example 2): 30g; S2: Add polyetheretherketone resin, carbon fiber, modified nano-silica, hydroxyapatite, coupling agent, and modified compatibilizer into a high-speed mixer in proportion and mix evenly; add the mixed material into a twin-screw extruder, set the melt temperature to 380°C, the screw speed to 300rpm, and extrude granulation; injection mold the granular material, the injection temperature is 360°C, and the mold temperature is 170°C, to obtain a modified polyetheretherketone composite material.
[0029] Example 9 Preparation of modified polyetheretherketone composite material: S1: Weigh polyetheretherketone resin: 850g; carbon fiber: 150g; modified nano-silica (prepared in Example 6): 200g; hydroxyapatite: 100g; coupling agent (methylvinyldimethoxysilane): 20g; modified compatibilizer (prepared in Example 3): 40g; S2: Add polyetheretherketone resin, carbon fiber, modified nano-silica, hydroxyapatite, coupling agent, and modified compatibilizer into a high-speed mixer in proportion and mix evenly; add the mixed material into a twin-screw extruder, set the melt temperature to 400°C, the screw speed to 400rpm, and extrude granulation; injection mold the granular material, the injection temperature is 380°C, and the mold temperature is 180°C, to obtain a modified polyetheretherketone composite material.
[0030] Comparative Example 1 A modified polyetheretherketone composite material, the raw material composition and process are basically the same as those of Example 8, the difference being that no modified compatibilizer is added to the component.
[0031] Comparative Example 2 A modified polyetheretherketone composite material, the raw material composition and process are basically the same as those of Example 8, the difference being that the modified compatibilizer added in the component is replaced by an equal weight of polyimide.
[0032] Comparative Example 3 A modified polyetheretherketone composite material, the raw material composition and process are basically the same as those in Example 8, except that the modified compatibilizer is replaced by a compatibilizer prepared by the following method: S1: Under nitrogen protection, add 400 ml DMAc, 40 g p-hydroxyacetophenone, and 55 g anhydrous K2CO3 to the reactor, stir and mix, heat to 110°C, then add 45 g 4-nitrochlorobenzene, react for 11 h, cool to 40°C, then add 100 ml anhydrous ethanol and 600 ml deionized water, stir, precipitate, filter, and then wash three times with deionized water (50 ml of deionized water each time), then add 300 ml anhydrous ethanol for recrystallization, and dry under vacuum at 60°C for 3 h to obtain intermediate 1; S2: Add 200 ml of anhydrous ethanol and 20 g of intermediate 1 to the reactor, stir, slowly and uniformly add 5 g of silicon tetrachloride at room temperature for 2 min, react at room temperature for 13 h, then add 100 ml of deionized water, continue stirring for 30 min, slowly add 10 wt% NaOH solution to adjust the solution to neutrality, filter, add 80 ml of deionized water for washing, and vacuum dry at 50 ° C for 3 h to obtain a trinitro compound; S3: Under nitrogen protection, add 200 ml of anhydrous ethanol, 20 g of a trinitro compound, and 0.7 g of Pd / C to the reactor, stir and mix, heat to reflux, and then slowly drop 6 g of hydrazine hydrate for 45 min. After reacting for 11 h, cool to room temperature, add 200 ml of deionized water, stir, precipitate, filter, and then wash three times with deionized water (50 ml of deionized water each time), and vacuum dry at 60 ° C for 3 h to obtain a fluorine-containing triamine monomer; S4: Under nitrogen protection, add 500g DMAc and 140g fluorine-containing triamine monomer into the reactor, add 90g 4,4'-(hexafluoroisopropylene) diphthalic anhydride in batches (30g in each batch, 5min interval between batches), stir, react at room temperature for 14h, then add 300ml acetic anhydride / pyridine mixture (acetic anhydride: pyridine (V:V) = 4:5), react at room temperature for 14h, then add 500ml anhydrous ethanol to produce precipitation, filter, wash with 35ml deionized water, and dry in vacuo at 50℃ for 4h to obtain the modified compatibilizer.
[0033] Comparative Example 4 A modified polyetheretherketone composite material, the raw material composition and process are basically the same as those in Example 8, except that the modified compatibilizer is replaced by a compatibilizer prepared by the following method: S1: Under nitrogen protection, add 400 ml DMAc, 40 g p-hydroxyacetophenone, and 55 g anhydrous K2CO3 to the reactor, stir and mix, heat to 110°C, then slowly drop 45 g 2-chloro-5-nitro-trifluoromethylbenzene, drop for 12 min, react for 11 h, cool to 40°C, then add 100 ml anhydrous ethanol and 600 ml deionized water, stir, precipitate, filter, and then wash three times with deionized water (50 ml of deionized water each time), then add 300 ml anhydrous ethanol for recrystallization, and dry under vacuum at 60°C for 3 h to obtain intermediate 1; S2: Add 200 ml of anhydrous ethanol and 20 g of intermediate 1 to the reactor, stir, slowly and uniformly add 5 g of silicon tetrachloride at room temperature for 2 min, react at room temperature for 13 h, then add 100 ml of deionized water, continue stirring for 30 min, slowly add 10 wt% NaOH solution to adjust the solution to neutrality, filter, add 80 ml of deionized water for washing, and vacuum dry at 50 ° C for 3 h to obtain a trinitro compound; S3: Under nitrogen protection, add 200 ml of anhydrous ethanol, 20 g of a trinitro compound, and 0.7 g of Pd / C to the reactor, stir and mix, heat to reflux, and then slowly drop 6 g of hydrazine hydrate for 45 min. After reacting for 11 h, cool to room temperature, add 200 ml of deionized water, stir, precipitate, filter, and then wash three times with deionized water (50 ml of deionized water each time), and vacuum dry at 60 ° C for 3 h to obtain a fluorine-containing triamine monomer; S4: Under nitrogen protection, add 500g DMAc and 140g fluorine-containing triamine monomer into the reactor, add 90g of pyromellitic anhydride in batches (30g in each batch, 5min interval between batches), stir, react at room temperature for 14h, then add 300ml of acetic anhydride / pyridine mixture (acetic anhydride: pyridine (V:V) = 4:5), react at room temperature for 14h, then add 500ml of anhydrous ethanol to produce precipitation, filter, wash with 35ml of deionized water, and dry in vacuo at 50℃ for 4h to obtain the modified compatibilizer.
[0034] Comparative Example 5 A modified polyetheretherketone composite material, the raw material composition and process are basically the same as those in Example 8, except that the modified compatibilizer is replaced by a compatibilizer prepared by the following method: (1) Dissolve 120 g of 4,4'-diaminodiphenyl ether in an appropriate amount of 500 g of N,N-dimethylformamide, then add 100 g of biphenyltetracarboxylic dianhydride, and stir to react for 24 hours to obtain a polyamic acid solution.
[0035] (2) The solution obtained in step (1) was mixed with 200 g of melamine, and the mixture was sealed and reacted at 200° C. for 8 h. After cooling, the mixture was poured into 200 ml of deionized water, and the precipitate was filtered off. The precipitate was then washed three times with deionized water (80 ml of deionized water was used each time), and vacuum dried at 60° C. for 3 h to obtain a modified compatibilizer.
[0036] Comparative Example 6 A modified polyetheretherketone composite material, the raw material composition and process are basically the same as those of Example 8, the difference being that the modified nano-silicon dioxide is replaced by nano-silicon dioxide of equal weight.
[0037] Comparative Example 7 A modified polyetheretherketone composite material, the raw material composition and process are basically the same as those in Example 8, the difference being that the modified nano-silicon dioxide is replaced by modified nano-silicon dioxide prepared by the following method: Add 500g toluene and 120g nano-silica to the reactor, ultrasonically shake for 20min, then add 40g γ-methacryloxypropyltrimethoxysilane and 60ml triethylamine, react at 100°C for 5h, centrifuge and wash, wash with 100ml toluene, 100ml anhydrous ethanol, and 100ml 50wt% ethanol in sequence, and then vacuum dry at 80°C for 2h to obtain silane-grafted nano-silica.
[0038] Comparative Example 8 A polyetheretherketone composite material is prepared by using the raw material composition and proportion of Example 2 of Chinese invention patent with publication number CN109851989A and the following method.
[0039] The polyetheretherketone resin used in Examples 7-9 and Comparative Examples 1-8 of the present application is RTP 2205HF BK, purchased from RTP Company of the United States; the carbon fiber is SYT55, purchased from Zhongfu Shenying Carbon Fiber Co., Ltd.; the nano-silicon dioxide particle size is 15nm, purchased from Shanghai Guipu Chemical Co., Ltd.; the hydroxyapatite is Fluoro-HA, purchased from Zhejiang Yamei Nano Technology Co., Ltd. When 2-chloro-5-nitro-trifluoromethylbenzene is added dropwise, the temperature of 2-chloro-5-nitro-trifluoromethylbenzene is 35°C.
[0040] The modified polyetheretherketone composite materials prepared in Examples 7-9 and Comparative Examples 1-8 were subjected to tests such as tensile strength, elongation at break, friction coefficient, and heat deformation temperature.
[0041] The tensile strength is based on GB / T1040.2-2006; the elongation at break is based on GB / T1040.2-2006; the friction coefficient is based on GB / T3960-2016; the heat deformation temperature is based on GB / T1634.1-2019; the salt spray test is conducted using the ASTM G85 standard, the sample size is 50×100×3mm (ISO 3167 standard dumbbell specimen), and the Appendix A5 dilute electrolyte cyclic spray / drying test method is used, with 50 cycles. The test results are shown in Table 1.
[0042] Table 1
[0043] It can be seen from Examples 7, 8 and 9 in Table 1 that the modified polyetheretherketone composite materials prepared by the present invention have a tensile strength greater than 112 MPa, an elongation at break greater than 22%, a friction coefficient less than 0.15, a heat deformation temperature of about 310°C, and have excellent tensile properties, wear resistance and corrosion resistance.
[0044] Comparative Example 1 is a comparative example without adding a modified compatibilizer. From the data in Table 1, it can be seen that its tensile strength is 81 MPa, the elongation at break is 16.4%, the friction coefficient is 0.26, the heat deformation temperature is 266°C, and the salt spray resistance is poor.
[0045] Comparative Example 2 is different from Example 8 in that the modified compatibilizer is replaced with an equal weight of polyimide. From the data in Table 1, it can be seen that the tensile strength is 85 MPa, the elongation at break is 17.2%, the friction coefficient is 0.24, and the heat deformation temperature is 274° C. Since the hyperbranched structure introduces physical crosslinking of the molecular chain, and the hyperbranched polyimide has good solubility, it promotes its uniform dispersion in the polyetheretherketone matrix and reduces defects, so the tensile strength and elongation at break of the composite material can be improved.
[0046] Comparative Example 3 is different from Example 8, and the difference is that 2-chloro-5-nitro-trifluoromethylbenzene in step S1 in the preparation process of the modified compatibilizer is replaced by 4-nitrochlorobenzene. It can be seen from the data in Table 1 that its tensile strength is 96MPa, the elongation at break is 18.6%, the friction coefficient is 0.22, and the heat deformation temperature is 297°C. This is because structural units such as fluorine-containing triamine monomers have good flexibility and reactivity, can form a "bridge" between polyetheretherketone and other components, reduce interfacial energy between phases, enhance interfacial bonding, make the distribution of each phase inside the composite material more uniform, and improve the overall performance.
[0047] Comparative Example 4 is a comparative example different from Example 8, the difference being that 4,4'-(hexafluoroisopropylene) diphthalic anhydride in step S4 during the preparation of the modified compatibilizer is replaced with pyromellitic anhydride. It can be seen from the data in Table 1 that its tensile strength is 101MPa, the elongation at break is 20.7%, the friction coefficient is 0.18, and the heat deformation temperature is 302°C. This is because the benzene rings, fluorine atoms, etc. contained in the modified compatibilizer have high thermal stability. In the composite material, it can interact with the polyetheretherketone molecular chain to improve the rigidity and thermal stability of the molecular chain, thereby increasing the heat deformation temperature of the composite material, so that it can maintain good performance in a higher temperature environment. At the same time, the introduction of fluorine atoms gives the material excellent chemical corrosion resistance. Furthermore, the fluorine-containing structure in the modified compatibilizer can form a stable protective film on the surface or interface of the composite material to resist the erosion of chemical substances and improve the stability and durability of the composite material in a chemical environment.
[0048] Comparative Example 5 is different from Example 8 in that the preparation process of the modified compatibilizer is different. It can be seen from the data in Table 1 that its tensile strength is 92 MPa, the elongation at break is 17.8%, the friction coefficient is 0.20, and the heat deformation temperature is 283°C.
[0049] Comparative Example 6 is different from the comparative example of Example 8, and the difference is that the modified nano-silica added in the component is replaced by unmodified nano-silica. It can be seen from the data in Table 1 that its tensile strength is 100MPa, the elongation at break is 20.3%, the friction coefficient is 0.19, and the thermal deformation temperature is 301°C. The surface of nano-silica is rich in hydroxyl groups (Si-OH), which are easily agglomerated through hydrogen bonds and van der Waals forces to form micron-sized aggregates, resulting in an increase in stress concentration points and a reduction in material strength. Through treatment with γ-methacryloxypropyltrimethoxysilane, the surface hydroxyl groups are replaced by hydrophobic groups, the polarity is reduced, the compatibility with the polyetheretherketone matrix is improved, and a three-dimensional network is formed through physical entanglement or chemical cross-linking, which can effectively disperse the external load and improve the tensile strength of the composite material.
[0050] In Comparative Example 7, the modified nano-silica added in the components is replaced by the silane-grafted nano-silica prepared in step S1. From the data in Table 1, it can be seen that the tensile strength is 102 MPa, the elongation at break is 20.9%, the friction coefficient is 0.17, and the heat deformation temperature is 308°C.
[0051] Comparative Example 8 is a polyetheretherketone composite material prepared by using the raw materials of Example 2 of Chinese invention patent publication number CN109851989A and the process of this application. It can be seen from the data in Table 1 that its mechanical properties and salt spray resistance are relatively poor.
[0052] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. However, any equivalent changes, modifications and evolutions made by ordinary technicians in the field without departing from the scope of the technical solution of the present invention by using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
Claims
1. A modified polyetheretherketone composite material, characterized in that: The invention comprises the following raw materials in parts by weight: Polyetheretherketone resin: 60-85 parts; carbon fiber: 5-15 parts; modified nano-silicon dioxide: 5-20 parts; hydroxyapatite: 5-10 parts; Coupling agent: 0.5-2 parts; Modified compatibilizer: 2-4 parts; The modified compatibilizer is prepared by the following method: S1: p-Hydroxyacetophenone and 2-chloro-5-nitro-trifluoromethylbenzene undergo nucleophilic substitution reaction in the presence of anhydrous K2CO3 to give intermediate 1; S2: Under the action of catalyst silicon tetrachloride, three molecules of intermediate 1 are condensed to undergo benzene cyclization reaction to obtain a trinitro compound; S3: The trinitro compound is reduced to a fluorine-containing triamine monomer under the action of a catalyst Pd / C and a reducing agent hydrazine hydrate; S4: Under nitrogen protection, add DMAc and fluorinated triamine monomer into the reactor, slowly drop 4,4'-(hexafluoroisopropylene) diphthalic anhydride, stir and react for 12-24 hours, then add acetic anhydride / pyridine mixture, and carry out ring-closing reaction at room temperature to obtain the modified compatibilizer.
2. A modified polyetheretherketone composite material according to claim 1, characterized in that: In the step S1, the mass ratio of p-hydroxyacetophenone to 2-chloro-5-nitro-trifluoromethylbenzene is 1:(1-1.25).
3. The modified polyetheretherketone composite material according to claim 1, characterized in that: In the step S2, the feed mass ratio of the intermediate 1 to silicon tetrachloride is 20:(4-6).
4. The modified polyetheretherketone composite material according to claim 1, characterized in that: In the step S3, the mass ratio of the trinitro compound, Pd / C and hydrazine hydrate is 20:(0.6-0.8):(5-8).
5. The modified polyetheretherketone composite material according to claim 1, characterized in that: In the step S4, the feed mass ratio of DMAc, fluorine-containing triamine monomer, and 4,4'-(hexafluoroisopropylene) diphthalic anhydride is 50:(12-16):(8-10).
6. The modified polyetheretherketone composite material according to claim 1, characterized in that: The coupling agent is one of vinyl triethoxysilane, 3-glycidyloxypropyl trimethoxysilane, and methyl vinyl dimethoxysilane, or a combination of several thereof.
7. The modified polyetheretherketone composite material according to claim 1, characterized in that: The preparation method of the modified nano silicon dioxide is as follows: S1: Add toluene and nano-silica to the reactor, perform ultrasonic vibration for 20-30 minutes, then add γ-methacryloxypropyltrimethoxysilane and triethylamine, react at 100-120°C for 3-5 hours, and post-treat to obtain silane-grafted nano-silica; S2: Under nitrogen protection, toluene, silane-grafted nano-silica, styrene and initiator AIBN are added into the reactor, stirred and mixed, heated to 80-100° C., reacted for 12-16 hours, and post-treated to obtain modified nano-silica.
8. The modified polyetheretherketone composite material according to claim 7, characterized in that: In step S1, the mass ratio of toluene, nano-silica and γ-methacryloxypropyltrimethoxysilane is 50:(12-16):(4-6).
9. The modified polyetheretherketone composite material according to claim 7, characterized in that: In step S2, the mass ratio of toluene, silane-grafted nano-silica, styrene, and initiator AIBN is 50:(8-10):(2-3):(0.02-0.05).
10. A method for preparing the modified polyetheretherketone composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Weigh 60-85 parts of polyetheretherketone resin, 5-15 parts of carbon fiber, and 5-20 parts of modified nano-silicon dioxide by weight; Hydroxyapatite: 5-10 parts; Coupling agent: 0.5-2 parts; Modified compatibilizer: 2-4 parts; S2: Add polyetheretherketone resin, carbon fiber, modified nano-silica, hydroxyapatite, coupling agent, and modified compatibilizer into a high-speed mixer in proportion and mix evenly; add the mixture into a twin-screw extruder, set the melt temperature to 360-400°C, the screw speed to 200-400rpm, and extrude granulation; injection mold the granular material, the injection temperature to 350-380°C, the mold temperature to 160-180°C, and obtain a modified polyetheretherketone composite material.
Citation Information
Patent Citations
Polyether ether ketone composite material and a preparation method and application thereof
CN109851989A
Polyether-ether-ketone cable material and preparation method thereof
CN103450631A
Polyetheretherketone-base composite, preparing method thereof and application thereof in friction reduction and wear resistance
CN104927298A
Polyether-ether-ketone wear resistant composite material, preparation method and application thereof in mechanical polishing retaining rings
CN105754288A
Preparation method of carboxylated polyimide reinforced carbon fiber composite polyether-ether-ketone material
CN118546404A
Cited By
High-performance PEEK composite material and application thereof in robot skeleton
CN120365725A
A PEEK composite material and its application in robot frame
CN120365725B